Here's the question you clicked on:
octoberchick1011
Solve the equation for H: S = LW + WH + HL
S = LW + WH + HL First, get all of the elements with H on one side. S - LW = WH + HL Then factor out the H: S - LW = H(W+L) Divide both sides by (W + L) (S - LW)/(W + L) = H. You're done!
So your final answer should be \[\frac{ S - LW }{ W + L }\]
Thank you so much!
No problem! :) It's not a terribly difficult thing to do, although working with letter variables (or constants) instead of numbers is always more intimidating. Good luck with the rest of your math!